Apparent therapy-resistant hypertension as risk factor for the development of type 2 diabetes mellitus. Issue 1 (January 2020) - Holtrop, Joris; Spiering, Wilko; Nathoe, Hendrik M.; De Borst, Gert J.; Kappelle, Laurens J.; De Valk, Harold W.; Visseren, Frank L.J.; Westerink, Jan
Abstract : Objective: To evaluate whether the relationship between hypertension and type 2 diabetes mellitus (T2DM) is different for patients with uncontrolled hypertension, controlled hypertension or patients with apparent therapy-resistant hypertension (aTRH), compared with patients without hypertension. Methods: Using Cox proportional hazard models we evaluated the risk of new-onset T2DM in 8756 patients, at high risk for vascular disease. Hypertensive patients were subdivided according to blood pressure (BP) and use of BP-lowering drugs. BP ≥ 140/90 mmHg was defined as uncontrolled BP. aTRH was defined as uncontrolled BP despite being treated with at least three BP-lowering drugs including a diuretic, or the use at least four BP-lowering drugs irrespective of BP levels. Further analysis evaluated the risk of new-onset T2DM for patients with uncontrolled hypertension and for patients with aTRH, compared with patients with controlled hypertension and without hypertension, respectively. Results: Forty-five percent had controlled hypertension, 20% had uncontrolled hypertension, 5.7% had aTRH, and 29% were nonhypertensive. During a follow-up of 7.0 (interquartile range: 0–14) years there were 705 new cases of T2DM. Patients with hypertension had a 1.48 (95% confidence interval 1.22–1.80) times higher risk of new-onset T2DM than nonhypertensive patients. There was no significant difference in risk among different hypertension groups. Conclusion: Patients at high risk for cardiovascular disease with hypertension have a 1.48 times higher risk of new-onset T2DM than nonhypertensive counterparts. The risk did not differ between patients with controlled hypertension, uncontrolled hypertension, or aTRH. Abstract : Supplemental Digital Content is available in the text